Lesson study : a Japanese approach to improving mathematics teaching and learning - Fernandez, Clea (Studies in mathematical thinking and learning., 2004)
Lesson study is a popular professional development approach in Japan whereby teachers collaborate to study content, instruction, and how students solve problems and reach for understanding in order to improve elementary mathematics instruction and learning in the classroom. This book is the first comprehensive look at the system and process of lesson study in Japan. It describes in detail the process of how teachers conducted lesson study--how they collaborated in order to develop a lesson, what they talked about during the process, and what they looked at in order to understand deepl.